Landslide-dammed lakes: a case study of the Lamabagar and Chaunrikharka landslide deposits, Dolakha and Solukhumbu districts, eastern Nepal - Uhlir, Christian F. (Journal of Nepal Geological Society, 1998)
The Lamabagar and Chaunrikharka landslides occurred within the gneisses of the Higher Himalayan lithotectonic unit both about 10 km north of the Main Central Thrust (MCT). Both landslide deposits are in the range of 10 to 100 million m3 and show an abnormal long stability, which confirms that the big size, the cohesiveness of the material and quick siltation of the impoundment are the most important factors for the longevity of natural dams. The Lamabagar landslide dam (Fig. 1) with a height of about 300 m is standing since more than three generations and the impoundment is completely silted up. The relics of the early postglacial Cbaunrikharka landslide dam (Fig. 2) with a former height of about 100 m and the eroded lake sediments of the Gath-Phakting area exposes excellently its inventory. The most probably annually layered bottom-set sediments south of Gath indicate a lifetime of the dam of about 120 years. Terraces within the canyon of Chaunrikharka document a periodical downcutting of the dam. The stable landslide dam of Lamabagar represents a prospective site for a hydroelectric plant of about 30MW.